Clinical outcomes of a defect-adapted strategy for free fibular great toe flaps in finger reconstruction: a retrospective series of 35 cases - Yangyang Liu; Huajian Zhou; Haoran Jiang; Jun Zhu; Renjie Li; Mingyu Jia (Journal of Plastic Surgery and Hand Surgery, 2026)
Background: To evaluate the clinical outcomes of a personalized surgical strategy for small-to-medium finger defects, utilizing either free dorsal toe or plantar proper digital artery flaps. Methods: We retrospectively analyzed 35 patients with finger defects (March 2021–January 2025). Patients were assigned by defect characteristics to Group A (pulp defects, n = 21; plantar proper digital artery flap) or Group B (dorsal/lateral defects, n = 14; modified dorsal toe artery flap preserving the plantar proper neurovascular bundle). We evaluated operative time, flap survival, Disabilities of the Arm, Shoulder and Hand (DASH), Michigan Hand Outcomes Questionnaire (MHQ), static two-point discrimination (s2PD), and American Orthopaedic Foot & Ankle Society (AOFAS) scores. Results: All 35 flaps survived. Group B had a significantly shorter mean operative time than Group A (124.00 ± 6.42 vs. 146.57 ± 9.61 minutes, p < 0.001). At final follow-up (6–13 months), Group B exhibited slightly better hand function (DASH: 5.89 ± 0.52 vs. 7.17 ± 1.00, p < 0.001; MHQ: 86.89 ± 2.82 vs. 83.61 ± 4.39, p = 0.018). Conversely, Group A achieved superior sensory recovery (s2PD: 7.48 ± 0.93 vs. 8.71 ± 0.83 mm, p < 0.001). Group B showed superior donor-site preservation without painful calluses (AOFAS: 96.08 ± 1.44 vs. 84.31 ± 2.19, p < 0.001).Conclusions: A tailored approach to donor vessel selection reliably guides personalized finger reconstruction. The plantar proper system optimizes pulp reconstruction for superior sensory recovery, whereas the modified dorsal system suits dorsal/lateral defects by minimizing operative time and maximizing donor-site protection.